How Teaching Online Impacts Safety and Comfort: Experiences of Students and Instructors in the Context of Learning Counseling Skills Online - Calderwood, Kimberly A.; Kvarfordt, Connie (International journal for the scholarship of teaching and learning, 2022)
The COVID-19 pandemic led to the necessity for many services to transition from in-person to online, including teaching in higher education and continuing education venues. This shift raised important pedagogical questions that have not yet been explored in the scholarship of teaching and learning literature. This study explored the experiences of students and instructors participating in a synchronous online four-day training workshop on counseling skills relating to supporting individuals who experience life stress and trauma. While many of the findings were consistent with what is already in the e-learning literature, new insights about safety and comfort emerged that have important implications for online delivery when teaching counseling skills and other topics involving potentially complex and emotional content. Recommendations for online teaching and future research are made.